2003
DOI: 10.1002/ccd.10431
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a closure device on complication rates in high‐local‐risk patients: Results of a randomized multicenter trial

Abstract: Clinical trials have shown that coronary stenting is associated with a high level of complications at the access site. Arterial sealing devices have proven their efficacy in obtaining immediate hemostasis after sheath removal, in allowing early ambulation, and in improving patient comfort. However, there is no report showing a reduction of local complications related to their use. The purpose of this multicenter study was to compare randomly the efficacy of Angio-Seal versus compression methods of hemostasis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
1
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(67 citation statements)
references
References 59 publications
2
63
1
1
Order By: Relevance
“…Similar procedures have a broad range of hemostatic complication rates for manual compression and VCD [10][11][12][13]. Depending on the definitions, the accuracy of follow-up protocols, and diagnostic tools used, complication rates as high as 64 % have been reported [14].…”
Section: Discussionmentioning
confidence: 99%
“…Similar procedures have a broad range of hemostatic complication rates for manual compression and VCD [10][11][12][13]. Depending on the definitions, the accuracy of follow-up protocols, and diagnostic tools used, complication rates as high as 64 % have been reported [14].…”
Section: Discussionmentioning
confidence: 99%
“…4 In another series, Chevalier et al reported, in a randomized study including 612 patients, reduction in mean homeostasis time from 52 to 5 minutes. 5 Hemorrhagic complications are the most common, with rates ranging between 5-7.4%, with 1.9% of episodes progressing with infection. There is a discussion as to whether this device could be a risk factor for infection for two reasons: excessive formation of hematomas, due to a risk known as endarteritis, and presence of a foreign body in the lumen and arterial wall, thus creating a niche for infection.…”
Section: Discussionmentioning
confidence: 99%
“…We identified complications arising from either VCD or MC by using corresponding International Classification of Disease Codes (ICD). We agreed upon the following complications and ICDcodes identified by literature search and after consultation of a clinician and a coder: hematoma and bleeding [3], arteriovenous fistula (AVF) [13], pseudo aneurysm [13], retroperitoneal haemorrhage (RPH) [14], thrombosis [14], infection of access site [14] and other complications as indicated by a ICD code relating to a complication occurring from a procedure. The risk for complication was assessed binary by either having one of these complications or having no complications at all.…”
Section: Measurement Of Expenditures and Complicationsmentioning
confidence: 99%